2014
DOI: 10.5604/12321966.1129929
|View full text |Cite
|
Sign up to set email alerts
|

Residential proximity to major roadways is associated with increased prevalence of allergic respiratory symptoms in children

Abstract: Our findings suggest an important spatial relationship between the distance from a major roadway and the evaluated respiratory symptoms. The results emphasize the need for more comprehensive air quality policies within urban areas with increased motor vehicle density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 27 publications
(29 reference statements)
4
22
0
Order By: Relevance
“…47 In contrast, studies that reported strong associations were conducted in places such as the United Kingdom, Poland, and South Korea, whose air pollution indexes were 40.63, 52.88, and 54.80, respectively. [23][24][25]48 Similar trends have been reported within the United States. A study conducted in Los Angeles reported that children and adults who suffer from asthma and live close to tra c are nearly three times more likely to visit the emergency department or be hospitalized than those who live near low tra c density.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…47 In contrast, studies that reported strong associations were conducted in places such as the United Kingdom, Poland, and South Korea, whose air pollution indexes were 40.63, 52.88, and 54.80, respectively. [23][24][25]48 Similar trends have been reported within the United States. A study conducted in Los Angeles reported that children and adults who suffer from asthma and live close to tra c are nearly three times more likely to visit the emergency department or be hospitalized than those who live near low tra c density.…”
Section: Discussionsupporting
confidence: 72%
“…[10][11][12] Areas close to major roadways can have high PM2.5 and CO levels, 13,14 and there is a growing body of evidence suggesting that proximity to car tra c sources can negatively affect asthma severity. [15][16][17][18][19][20][21][22][23][24][25][26] Importantly, the results of these studies are somewhat mixed, with a few studies either nding no association or weak associations between asthma exacerbations and distance to roadways. [27][28][29][30] Some of the inconsistency in the results can be attributed to heterogeneity in study design, outcomes, cohort de nition, and exposure assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, allergies and wheezing showed much stronger associations with living near non-interstate primary roads than with living near the interstate, but associations were not statistically significant. Porebski et al (2014) found similar results among children and adolescents, comparing those living < 200 m from major roadway versus those living further than 500 m from the nearest major roadway, statistically significant odds ratios ranged from 2.0 to 5.7 for self-reported asthma and asthma symptoms. Bowatte et al (2016) also found a slightly increased odds ratio of 1.10 (0.97–1.24) among an adult population when comparing those living within 200 m of a major road with those living further away.…”
Section: Discussionmentioning
confidence: 53%
“…As explained by [20], the use of population density as a proxy for exposure levels is motivated by the fact that (i) exposure to local emissions from transport is largely a function of both the amount of traffic activity, and the number of people who regularly live or work along roadsides [50,53]; that (ii) numerous studies analyze air pollutant exposure levels at a certain distance from a high-traffic road [54,55]; and that (iii) health effects and residential proximity to high traffic roads show a correlation [51].…”
Section: Assessment Indicatorsmentioning
confidence: 99%